MASYARAKAT INDONESIA DALAM SERIBU WAjAH KAPITALISME - Luthfi, Asma (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Basically, the existing capitalist system in Indonesia today is the economic system that has beenÃ‚Â practiced for a long time. Throughout its history, there are several forms of the capitalist system thatÃ‚Â has been practiced in Indonesia. The frst is the colonial capitalist system which lasted from the DutchÃ‚Â colonial period until IndonesiaÃ¢â‚¬â„¢s independence. The second is the bureaucratic capitalism that took placeÃ‚Â during the New Order period. The third is the global capitalist system that emerges when neo-liberalismÃ‚Â policies are applied to the Third-World countries, including Indonesia. Such capitalist systems in theirÃ‚Â developments give either some implications or impacts to the social life of the people in Indonesia.Keywords: Indonesia peopleÃ¢â‚¬â„¢s, capitalist system